Petrobras, pré-sal e a (des)industrialização - Vicente, Jackeline Bertuolo Barron Guerra (2015)
This work aims at analysing the impacts associated with oil extraction from the Brazilian pre-salt layers, particularly those concerning the balance of trade, the Dutch disease and the deindustrialization process. We present data indicating that Brazil is facing a deindustrialization process due, to a great extent, to the effects of the Dutch disease, which is evident from the reduction of the manufacturing sector s contribution to GDP and from the increasing importance of primary goods exports in the export basket. We consider the potential for wealth creation, the negative impacts associated with oil extraction from pre-salt layers and suggest some alternatives to minimize such impacts. Hence, in order to avoid further aggravation of foreign exchange and deindustrialization problems due to pre-salt oil exports, we present a number of suggested measures, with an emphasis on consistent industrial policies, capable of stimulating various segments, thus reverting the deindustrialization process and directing pre-salt revenues towards the country s social and economic development. Petrobras, the state-owned oil sector company, has played and still plays a strategic role in pre-salt oil discovery and extraction. Moreover, it can be used to foster investments as a way of stimulating the development of its corresponding chain of goods and services